Rotating machinery, hybrid test methods, vibro-acoustics & laser vibrometry. proceedings of the 34th IMAC, a Conference and Exposition on Structural Dynamics 2016 /: proceedings of the 34th IMAC, a Conference and Exposition on Structural Dynamics 2016. Volume 8 : (2016) - Unknown
No abstract available